2015
DOI: 10.1038/srep16480
|View full text |Cite
|
Sign up to set email alerts
|

Electric field induced reversible 180° magnetization switching through tuning of interfacial exchange bias along magnetic easy-axis in multiferroic laminates

Abstract: E-field control of interfacial exchange coupling and deterministic switching of magnetization have been demonstrated in two sets of ferromagnetic(FM)/antiferromagnetic(AFM)/ferroelectric(FE) multiferroic heterostructures, including NiFe/NiCoO/glass/PZN-PT (011) and NiFe/FeMn/glass/PZN-PT (011). We designed this experiment to achieve exchange bias tuning along the magnetic easy axis, which is critical for realizing reversible 180° magnetization deterministic switching at zero or small magnetic bias. Strong exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…A similar result was also reported by Xue et al [327] and it implies that AFM/FM/FE multiferroic heterostructures are prototypes to tune exchange coupling by electric fields and constitute an important step toward a practical MRAM at room temperature.…”
Section: Magnetization Switching Assisted By a Small Magnetic Fieldsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar result was also reported by Xue et al [327] and it implies that AFM/FM/FE multiferroic heterostructures are prototypes to tune exchange coupling by electric fields and constitute an important step toward a practical MRAM at room temperature.…”
Section: Magnetization Switching Assisted By a Small Magnetic Fieldsupporting
confidence: 86%
“…However, it is a great challenge to break the limits of 90° switching magnetization without the assistance of a magnetic field or spin-transfer torque. An alternative method to replace the external magnetic field is the introduction of an electric field [327,328]. The manipulation of magnetization reversal by a pure electric field rather than a magnetic field has been reported by some groups [51,52,59], which illuminates the direction of magnetic field-free switching in the future.…”
Section: Electric Field-driven Magnetization Reversalmentioning
confidence: 99%
“…Heron et al [116] approached this issue through E-field control of exchange bias in multiferroic/magnetic (CoFe/BiFeO 3 ) heterostructures. Xue et al [117] demonstrated that the E-field induced near 180˝magnetization switching in the AFM/FM/FE heterostructures through voltage-controlled tuning of exchange bias and through manipulation of coercive fields. The irreversibility of the E-field induced near 180˝magnetization switching in AFM/FM/FE heterostructures was resolved by employing a magnetic impulse, which could switch the magnetization back and lead to a continuous magnetization switching [118].…”
Section: Magnetoelectric Random Access Memorymentioning
confidence: 99%
“…Figure 3 shows diffractograms of the films deposited at substrate temperatures of 17, 100, 200, 400, 500, and 600 °C. The XRD patterns show peaks corresponding to the FeMn and NiFe layers to have the fcc structure with (111) orientation that is usually observed in such structures [ 28 , 29 , 30 , 31 ]. Moreover, one can see that the peak intensity of the FeMn layer decreases with the increasing substrate temperature, while the width of the FeMn peaks increases with the increasing T SUB .…”
Section: Resultsmentioning
confidence: 99%